Growth performance and fibre utilization of Murrah male buffalo calves fed wheat straw based complete feed blocks incorporated with superior anaerobic fungal zoospores (Neocallimastix sp. GR-1) - KUMAR, SANJAY; SEHGAL, J P; PUNIYA, A K; KUMARI, RAJNI (The Indian Journal of Animal Sciences, 2015)
In vivo study was designed to assess the influence of anaerobic fungal zoospores of Neocallimastix sp. GR-1, incorporated in wheat straw based complete feed blocks on growth performance, nutrient utilization, ruminal fermentation pattern and nutritive evaluation in terms of digestible crude protein (DCP) and total digestible nutrients (TDN) in male calves. Male Murrah buffalo calves (12), 5–7 months -old, weighing 82±6.60 kg, were randomly divided into 2 equal groups of 6 each. Animals in control group were fed a complete feed blocks (consisting of 50:50 wheat straw: concentrate mixture) along with 2 kg green maize fodder/animal/d. Treatment group of animals were fed with complete feed blocks as those for control group but incorporated with fungal zoospores of Neocallimastix sp. GR-1 to about 140 × 106 zoospores/ block of 14 kg along with 2 kg green maize/animal/d. Daily feed intake and fortnightly body weights of all the calves were recorded during the 172 d experimental period. After 90 d of experimental feeding a digestibility trial of 7 d duration was conducted and samples from feed blocks, green maize, faeces and refusals were collected. After 150 d of experimental period, samples of rumen liquor were collected through stomach tube before feeding (at 0 h) for 3 consecutive days. The results showed 16% increase in body weight gains of calves of zoospores incorporated ‘Z’ group of animals over the control group ‘C’ with similar daily feed intake. Also % feed efficiency enhanced by 28.7% over the control diet. The digestibility of DM, OM, CP, CF, NDF, ADF, ADL and cellulose of complete feed blocks increased significantly in treatment group. The digestible energy value in terms of %TDN also enhanced significantly in treatment group compared to control group. The pH, NH3-N and protozoan count/mL were lower, whereas total-N, TCA-N, TVFAs, number of fungal zoospore and bacteria/mL in rumen liquor were significantly higher in treatment group indicating that the nutritive value of wheat straw based complete feed blocks can be enhanced with the incorporation of elite fungal zoospores. This technology developed to improve the nutritive value of wheat straw based diets, can be used at the compound feed industry level for providing a well balanced wheat straw based complete feed rations to the animals at farmers door.